Regression Model of Stakeholder Implementation on CSR Performance: A Quantitative Approach to State-Owned Enterprises in the Digital Era 2025 - Aisyah Amini Hasibuan; Mahameru Rosy Rochmatullah (Majapahit Journal of Islamic Finance and Management, 2026)
The manner in which SOEs carry out CSR has undergone a significant transformation thanks to digitalization. The goal of this research is to examine how stakeholder implementation affects CSR performance in state-owned enterprises in the digital age of 2025. For the years 2021–2025, 25 Scopus Q1-Q3 indexed publications were systematically reviewed using the PRISMA 2020 methodology. The study found that stakeholder implementation improves CSR performance, with primary stakeholders' orientation having a greater impact than secondary stakeholders'. Through greater transparency and dynamic skills, digital transformation plays a complicated moderating role that improves relationships. There were notable variations between sectors, with consumer market businesses enjoying greater long-term benefits. In conclusion, in order to maximize sustainable CSR performance, SOEs must prioritize digital transformation and sector-specific methodologies in the development of an integrated stakeholder implementation strategy.